Spectrophotometric Estimation of Formoterol Fumerate in Pharmaceutical Formulations - PRAKASH, K.VANITHA; VENKATESWARA RAO, J.; APPALA RAJU, N.; HIMABINDU, V. (Asian Journal of Chemistry, 2010)
Three simple, accurate, rapid and sensitive methods (A, B and C) have been developed for the estimation of formoterol fumerate in its pharmaceutical dosage form. The method A is based on the formation of blue coloured chromogen, due to reaction of formoterol fumerate with Folin Ciocalteu reagent in the presence of alkali, which exhibits λmax at 730 nm. Method B is based on the reduction of ferric ions of the reagent ferric chloride to ferrous ions by the drug, which further in the presence of potassium ferricyanide as oxidizing agent produces blue coloured chromogen measured at 700 nm, against reagent blank. The method C is based on the formation of red coloured chromogen with ferric chloride and 1,10-phenanthroline, which shows absorption maximum at 520 nm. The absorbance-concentration plot is linear over the range of 1-12 mcg/mL for method A, 1-10 mcg/mL for method B and 1-12 mcg/mL for method C. Results of analysis for all the methods were validated statistically and by recovery studies. The proposed methods are economical and sensitive for the estimation of formoterol fumerate in bulk drug and in its formulations (Rotacap).